(untitled) (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Objectives: To describe preoperative psychological status and analyze associated factors among patients at Vinmec Da Nang Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 183 patients undergoing elective surgery from April to October 2024. Preoperative anxiety and information needs were assessed using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data were collected through direct interviews and analyzed using SPSS 20.0. Associations were examined using Chi-square and Fisher’s exact tests with p<0.05 considered statistically significant. Results: Preoperative anxiety was found in 96.2% of patients, including 61.7% with moderate anxiety and 35.5% with high anxiety. Information needs were reported by 95.6% of patients, with moderate and high levels accounting for 49.7% and 47%, respectively. Major concerns included anesthesia methods and surgical procedures (97.8%), postoperative pain (85.2%), intraoperative complications (76.5%), and anesthesia-related complications (72.1%). Age and educational level were significantly associated with preoperative psychological status (p<0.05). Conclusions: A high prevalence of anxiety and information needs was identified among preoperative patients; routine psychological assessment is essential to improve comprehensive patient care.